Item bias elimination models for test reliability and validity - Pedrajita, Jose Q. (2007)
The issue of bias in measurement has come to the forefront of controversy over testing practices. This study looked into class bias, gender bias, and ability bias in a Chemistry Achievement test. It also examined the effect of biased items elimination on the content and concurrent validity, and internal consistency reliability of the original as well as the versions. Two hundred junior high school students participated in the study. The descriptive comparative reasearch design utilizing item bias detection and elimination, and validity and reliability analysis was employed. Findings revealed the presence of class bias, gender bias, and English ability bias in the Chemistry Achievement Test.